Analisis Zat Besi (Fe), dan Organoleptik Cookies Substitusi Tepung Hati Ayam dan Tepung Kacang Hijau (Vigna Radiata L.) - Wahyuning Tyas, Dhea; Purnama Sari, Dwi Kurnia; Ainun Nafies, Dian Ayu (Media Gizi Ilmiah Indonesia, 2025)
Anemia is one of the most common nutritional problems throughout the world, not only in developing countries but also in other developed countries. Anemia is a condition in which the number of red blood cells or hemoglobin is below normal limits if the hemoglobin level is <14 g/dL in men and <12g/dL in women. To provide additional iron (Fe) to adolescents, it is hoped that by making cookies substituting chicken liver flour and green bean flour (Vigna Radiata L.) it can be used as an alternative snack for adolescents. The purpose of this study was to determine the effect of substitution of chicken liver flour and green bean flour (Vigna Radiata L.) on iron (Fe) levels and acceptability test on cookies. This research used True Experimental with Completely Randomized Design (CRD), 4 treatment levels and 6 times replication. The treatment applied was the ratio of wheat flour: chicken liver flour: mung bean flour at each P0 (100:0:0), P1 (45:25:30), P2 (30:40:30), P3 (25:30:45). The results of the study showed that there was an effect on increased iron (Fe) levels, with the highest iron (Fe) levels in the P3 treatment. There was a significant effect on color, taste, aroma and texture (Kruskall-Wallis (p<0.005). The best effect was on cookies treated with P1. The conclusion of this study was that cookies substituted for chicken liver flour and mung bean flour have an influence on iron (Fe) levels, and organoleptic quality.